IA spring '98 report, Bill Huser - Huser, Bill F.et al (1998)
An annotated list of birds sighted by Bill Huser and two others. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1998. Epson - sheet feed